Effects of pilates exercises on spine deformities and posture: a systematic review - Li, Fangyi; Omar Dev, Roxana Dev; Soh, Kim Geok; Wang, Chen; Yuan, Yubin (Springer Science and Business Media LLC, 2024)
Background Pilates is becoming increasingly popular amongst a wide range of people and is gaining more attention. It is also an efective means of physical rehabilitation. The aim of this systematic review is to explore the efects of Pilates on spinal deformity and posture. Method This systematic review was conducted using four recognised academic and scientifc databases (Scopus, Web of Science, PubMed and Cochrane) to identify articles that met the inclusion criteria. The secondary search used the Google Scholar and the Science Direct search engines. The search for articles for this review began in July 06, 2023 and was concluded on February 01, 2024. The search process for this study was documented using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020). The PEDro scale was used to assess the internal validity and data statistics of the studies included in this systematic review and to evaluate the quality of the studies. Results The systematic review included nine studies that met the inclusion criteria from the 651 studies retrieved, involving a total of 643 participants. The PEDro scale scores of the studies included in this systematic review ranged from 3 to 8. The intervention was in the form of Pilates or Pilates combined exercises. The studies included in this review used outcome measures of Cobb angle, angle of trunk rotation (ATR), range of motion (ROM), chest expansion, Scoliosis Research Society Questionnaire (SRS-22r) and postural assessment. Research has shown that Pilates is efective in correcting spinal deformities and posture, as well as improving quality of life, pain relief, function and ftness. Conclusions This systematic review provide substantial evidence that Pilates has a positive impact on improving spinal deformity and posture. However, more research is needed to validate whether Pilates can be used efectively as a physical therapy for spinal deformity rehabilitation. Pilates has considerable potential for public health interventions.